Growth-maximizing public debt in Turkey: An empirical investigation - Bulus, Gokay Canberk (Economics and Business Review, 2020)
The aim of the paper is to empirically estimate the growth-maximizing debtto-GDP ratio in the case of Turkey. To calculate the growth-maximizing debt-to-GDPratio FMOLS, DOLS, and CCR estimators are used for the period from 1960–2013.According to the empirical findings the growth-maximizing debt-to-GDP ratio variesbetween 34.3% and 38.7%. Based on a comparison of these ratios to current data(29.1% for 2018), Turkey has the capacity for additional borrowing to achieve a growthmaximizingdebt-to-GDP ratio. If this additional borrowing capacity is used for publicinvestment with a return greater than the interest cost of the additional debt economicgrowth will be maximized and public debt sustainability supported.